1372 Thrombocytosis and Malignancy: Management in Primary Care. (12th October 2021) - Choi, B; Jegatheeswaran, L; Platt, E
Abstract: Introduction: The diagnosis of cancer relies within primary care to recognise this possibility in patients. Studies have shown an association of thrombocytosis with cancer, in particular lung, renal, uterine and colorectal cancer. Subsequently, suspected cancer pathways incorporate thrombocytosis in stratifying risk. This quality improvement project aimed to evaluate and improve the approach of GPs at a West London practice in managing thrombocytosis. Method: A retrospective study evaluated patients with a most recent platelet count of > 450x109/L. Furthermore, a survey was sent to all GPs within the practice to establish their understanding and concerns. Results were presented locally, and intervention applied following the end of the first cycle. Results: The survey showed 75% (n = 9) of staff were aware of the association of thrombocytosis and malignancy. In absence of specific symptoms, 64% would consider a chest X-ray, 41% a faecal occult blood test and 16% would consider transvaginal USS in women. 28 patients were identified with thrombocytosis. Of these, 4 had underlying malignancy, 3 had an underlying haematological condition. 2 cases had a concurrent inflammatory process. Of the remaining 19 patients, 5 were referred on for specialist service. In the remaining 14, although filed as "to repeat blood test" or "speak to doctor", 12 had yet to be actioned. Conclusions: The management of thrombocytosis at a local level in primary care has room for improvement. An alert was designed and created on the online system used by the practice to safeguard missed recalls for blood tests and prompts to consider the possibility of malignancy.